A new windings design for improving single-phase induction motor performance - Zuriman Anthony; Erhaneli Erhaneli; Yusreni Warmi; Zulkarnaini Zulkarnaini; Anggun Anugrah; Sepannur Bandri (Institute of Advanced Engineering and Science, 2022)
Single-phase induction (asynchronous) motors are widely used at home. These motors have two windings and usually operate at a lower performance than 3-phase asynchronous motors which have three windings. For this reason, this study aims to design a new winding of a single-phase asynchronous motor by increasing the number of phases in the motor windings in order to increase the performance of the motor. This research was focused on 36 slot capacitor-start capacitor-run asynchronous motor. The design used 4 non-identical windings in the motor, where three windings acted as auxiliary windings and one winding acted as main winding. The rated current of the designed motor winding was 2.74 A for the main winding and 3.15 A for the auxiliary winding. The performance of the designed motor compared to the traditional single-phase asynchronous motor with the same structure of stator, rotor, and rated current. A traditional single-phase asynchronous motor had data: 1 HP, 220 V, 8.3 A, 1440 RPM, 50 Hz, and 4 poles. The results of this study indicated that the designed motor operated with power factors almost close to unity and had higher output power, torque, and efficiency than the traditional single-phase asynchronous motors.